MRC2 Expression Correlates with TGFβ1 and Survival in Hepatocellular Carcinoma - Gai, Xiaohong (MDPI, 2014)
MRC2 (Mannose Receptor C Type 2) is a constitutively recycling endocytic receptor belonging to the mannose receptor family, which has been found to be closely involved with cancer metastasis. This study attempted to determine MRC2 expression on hepatocellular carcinoma (HCC) and its significance on postsurgical prognosis of HCCs. The expression of both MRC2 and transforming growth factor (TGFβ1) was detected in tumor tissues and adjacent liver tissues from 96 HCCs by immunohistochemistry staining, and it was found that MRC2 expression in HCC tissues was significantly higher than in adjacent liver tissues. HCCs with higher MRC2 expression had worse prognosis after liver resection. Univariate analysis showed that advanced TNM staging of HCC, higher Edmonson-Steiner classification, intrahepatic metastases, portal vein invasion, higher MRC2 and higher TGFβ1 were the poor prognostic factors. Furthermore, multivariate analysis revealed that intrahepatic metastases, higher MRC2 and higher TGFβ1 were the independent prognostic factors. TGFβ1 treatment up-regulated MRC2 expression, cell migration and invasion of Huh7 cells notably. In addition, knockdown of MRC2 repressed the effect of TGFβ1 on cell migration and invasion. These data suggest that MRC2 overexpression predicts poor prognosis of HCCs after liver resection and MRC2 potentially contributed to TGFβ1-driven up-regulation of cell migration and invasion in HCC.